2016
DOI: 10.18632/oncotarget.9889
|View full text |Cite
|
Sign up to set email alerts
|

Multi-targeting NGR-modified liposomes recognizing glioma tumor cells and vasculogenic mimicry for improving anti-glioma therapy

Abstract: Like the anti-angiogenic strategy, anti-vascular mimicry is considered as a novel targeting strategy for glioma. In the present study, we used NGR as a targeting ligand and prepared NGR-modified liposomes containing combretastatin A4 (NGR-SSL-CA4) in order to evaluate their potential targeting of glioma tumor cells and vasculogenic mimicry (VM) formed by glioma cells as well as their anti-VM activity in mice with glioma tumor cells. NGR-SSL-CA4 was prepared by a thin-film hydration method. The in vitro targeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…Liu et al [5] demonstrated that VM-positive glioma patients have a poorer prognosis than patients with VM-negative gliomas. Ju et al [9], Huang et al [33], and Ying et al [34] proved that liposomes containing VM-targeting drugs improve anti-glioma therapy in orthotopic glioma-bearing nude mice. In agreement with the above findings, our in vitro and in vivo results showed that the destruction of VM formation by HOXA-AS2 knockdown impaired glioma malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [5] demonstrated that VM-positive glioma patients have a poorer prognosis than patients with VM-negative gliomas. Ju et al [9], Huang et al [33], and Ying et al [34] proved that liposomes containing VM-targeting drugs improve anti-glioma therapy in orthotopic glioma-bearing nude mice. In agreement with the above findings, our in vitro and in vivo results showed that the destruction of VM formation by HOXA-AS2 knockdown impaired glioma malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro cytotoxicity of CLA-PTX@PEG NPs was evaluated in B16-F10 cells, MDA-MB-231 cells and U87-MG cells using the sulfonylrhodamine B (SRB) assay182123. The half-maximal inhibitory concentration (IC 50 ) was calculated according to the dose-effect curves using GraphPad Prism 6 software.…”
Section: Methodsmentioning
confidence: 99%
“…8 Under the condition of hypoxia, tumor cells could directly form VM channels, thus facilitating tumor metastasis without the involvement of endothelial cells. [9][10][11] VM channels have been observed in a variety of malignant tumors including NSCLC and may provide sufficient blood perfusion for the rapid tumor growth. Increasing studies indicated that a poor prognosis in lung cancer patients was associated with the emergence of the VM channels.…”
Section: Introductionmentioning
confidence: 99%